On a New Class of Finite Integrals Involving Generalized Hypergeometric Function: K. Shantha Kumari, Arjun K. Rathie, Shwetha S. Shetty - Team, Support (Thai Journal of Mathematics, 2022)
The main aim of this research paper is to obtain fifty new class of integrals involving generalized hypergeometric function in the form of two master formulas.One hundred interesting integrals have been obtained as special cases of our main findings. The results are established with the help of generalized Watson's summation theorem obtained earlier by Lavoie, et al. and an interesting integral due to MacRobert.